Sirtuin 5 is Dispensable for CD8+ T Cell Effector and Memory Differentiation - Duan, Qianqian; Ding, Jiying; Li, Fangfang; Liu, Xiaowei; Zhao, Yunan; Yu, Hongxiu; Liu, Yong; Zhang, Lianjun (Frontiers in Cell and Developmental Biology, 2021)
CD8+ T cell effector and memory differentiation are tightly controlled at multiple levels including transcriptional, metabolic and epigenetic regulation. Sirtuin 5 (SIRT5) is a protein deacetylase mainly located at mitochondria, but it remains unclear whether SIRT5 plays key roles in regulating CD8+ T cell effector or memory formation. Herein, with adoptive transfer of Sirt5+/+ or Sirt5-/- OT-1 cells and acute Listeria monocytogenes infection model, we demonstrate that SIRT5 deficiency does not affect CD8+ T cell effector function and SIRT5 is not required for CD8+ T cell memory formation. Moreover, the recall response of SIRT5 deficient memory CD8+ T cells is comparable with Sirt5+/+ memory CD8+ T cells. Altogether, these observations suggest that SIRT5 is dispensable for the effector function and memory differentiation of CD8+ T cells.